miR-21 mediates hematopoietic suppression in MDS by activating TGF-β signaling. - Bhagat, T; Zhou, L; Sokol, L; Kessel, R; Caceres, G; Gundabolu, K; Tamari, R; Gordon, S; Mantzaris, I; Jodlowski, T; Yu, Y; Jing, X; et al. (American Society of Hematology, 2013)
Myelodysplastic syndromes (MDS) are characterized by ineffective hematopoiesis that leads to peripheral cytopenias. We observed that SMAD7, a negative regulator of transforming growth factor-beta (TGF-β) receptor-I kinase, is markedly reduced in MDS and leads to ineffective hematopoiesis by overactivation of TGF-β signaling. To determine the cause of SMAD7 reduction in MDS, we analyzed the 3'UTR of the gene and determined that it contains a highly conserved putative binding site for microRNA-21. We observed significantly elevated levels of miR-21 in MDS marrow samples when compared with age-matched controls. miR-21 was shown to directly bind to the 3'UTR of SMAD7 and reduce its expression in hematopoietic cells. Next, we tested the role of miR-21 in regulating TGF-β signaling in a TGF-β-overexpressing transgenic mouse model that develops progressive anemia and dysplasia and thus serves as a model of human bone marrow failure. Treatment with a chemically modified miR-21 inhibitor led to significant increases in hematocrit and led to an increase in SMAD7 expression in vivo. Inhibition of miR-21 also led to an increase in erythroid colony formation from primary MDS bone marrow progenitors, demonstrating its ability in stimulating hematopoiesis in vitro. Taken together, these studies demonstrate the role of miR-21 in regulating overactivated TGF-β signaling in MDS.